NGHIÊN CỨU SẢN XUẤT DIESEL SINH HỌC CHẤT LƯỢNG CAO TỪ VI TẢO BIỂN TETRASELMIS SP. - Thị Ngọc Mai, Đinh; Thị Thơm, Lê; Cẩm Hà, Nguyễn; Đình Lãm, Bùi; Lan Anh, Hoàng; Diễm Hồng, Đặng (Vietnam Journal of Science and Technology, 2017)
The world is facing declining fossil fuel reserves at a time when energy demand is exploding. In this context, biodiesel attracts increasing attention worldwide as a clean energy for the future to substitute conventional fuel. However, the lack of oil feedstocks limits the large-scale development of biodiesel to a large extent. Recently, microalgae have long been identiﬁed as a potential feedstock due to their many advantages for biodiesel production. Compared to traditional feedstocks such as rapeseed, jatropha and soybean, microalgae can rapidly grow on nonagricultural land or in brackish water with high oil content, rapid growth rate, less affection by venue, season and climate, and easier to scale up. Moreover, they can absorb carbon dioxide as the carbon source for growth. This work was undertaken to obtain high quality biodiesel production from a local marine microalga Tetraselmis sp. The in situ acidcatalysed transesterification resulted in a biodiesel yield of 71 % based on algal oil. The prediction values of density at 15 0C, viscosity at 40 0C, flash point, iodine value, cetane number meet the B100 biodiesel quality standard of Vietnam. In addition, the structural morphology and lipid staining of Tetraselmis sp. were also studied.